Complete moment convergence of weighted sums for arrays of negatively dependent random variables and its applications. Issue 11 (2nd June 2016) - Wu, Yongfeng; Volodin, Andrei
ABSTRACT: The authors study the complete moment convergence of weighted sums for arrays of rowwise negatively dependent random variables. The obtained results improve the corresponding results of Baek and Park(2010) . Convergence of weighted sums for arrays of negatively dependent random variables and its applications. As an application, the authors obtain the complete moment convergence of linear processes based on pairwise negatively dependent random variables. In addition, the authors point out a gap of the proof in Baek and Park(2010) and raise an open problem.